2004
DOI: 10.1111/j.1600-4469.2004.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress–strain response in human dentine: rethinking fracture predilection in postcore restored teeth

Abstract: In this study, the biomechanical perspective of fracture predilection in post-core restored teeth is investigated using computational, experimental, and fractographic analyses. The computational finite element analysis and the experimental tensile testing are used to evaluate the stress-strain response in structural dentine. The fractographic evaluations are conducted using laser scanning confocal microscopy and scanning electron microscopy to examine the topography of dentine from experimentally fractured spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 17 publications
4
76
0
2
Order By: Relevance
“…Regions of stress-strain concentration are interpreted as potentiators of crack initiation and propagation (122). This method lends itself to simulation of different loads applied to the tooth structure, both static and dynamic, as well as different types of restorations present.…”
Section: Discussionmentioning
confidence: 99%
“…Regions of stress-strain concentration are interpreted as potentiators of crack initiation and propagation (122). This method lends itself to simulation of different loads applied to the tooth structure, both static and dynamic, as well as different types of restorations present.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that the preparation of endodontic access cavities reduces the strength of the teeth, because of deep and extended cavity preparations which critically reduce the amount of dentin (4)(5)(6)(7)(8) and increase cuspal deflection during function (9). The importance of conserving the bulk of dentin was demonstrated in maintaining the structural integrity and in the prognosis of endodontically restored teeth (10)(11)(12)(13), as the fracture resistance and stress distribution of endodontically treated teeth is directly affected by the amount of residual coronal dentin (4,(14)(15)(16)(17)(18). In posterior preparations, especially when the cervical margin is located in dentin, the polymerization shrinkage effects can be significant, producing marginal defects and gaps despite careful application (19).…”
Section: Introductionmentioning
confidence: 99%
“…Endodontically-treated teeth present different responses to mechanical loads from intact teeth. The removal of pulp and root dentin diminishes a protective feedback mechanism and reduces the stress-strain capacity of the teeth, compromising the root fracture resistance [4,28]. The stability of the teeth is reduced by endodontic preparative procedures, leading to more root deformations and less stiffness [29,30].…”
Section: Discussionmentioning
confidence: 99%